2020
DOI: 10.3390/ijerph17134750
|View full text |Cite
|
Sign up to set email alerts
|

Is Narcissism Associated with Heavy Work Investment? The Moderating Role of Workload in the Relationship between Narcissism, Workaholism, and Work Engagement

Abstract: This study aimed to investigate the association between narcissism and two forms of heavy work investment, namely, workaholism and work engagement. More specifically, it was hypothesized that narcissism is positively associated with both workaholism and work engagement, with workload moderating these relationships, which are expected to be stronger when the workload is high. Overall, 217 workers completed a self-report questionnaire, and the hypothesized relationships were tested using moderated multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 92 publications
(165 reference statements)
0
18
0
Order By: Relevance
“…In this case, our results confirm that workaholics could be less influenced by this personality trait. Apparently, contrary to this conclusion, Falco et al [ 48 ] found a strong correlation between workaholism and narcissism (measured by the NPI that predominantly measures the grandiose face of narcissism), a construct related to neuroticism. However, there is evidence that neuroticism is mostly related to the vulnerable face of narcissism, rather than the grandiose one [ 49 ].…”
Section: Discussionmentioning
confidence: 92%
“…In this case, our results confirm that workaholics could be less influenced by this personality trait. Apparently, contrary to this conclusion, Falco et al [ 48 ] found a strong correlation between workaholism and narcissism (measured by the NPI that predominantly measures the grandiose face of narcissism), a construct related to neuroticism. However, there is evidence that neuroticism is mostly related to the vulnerable face of narcissism, rather than the grandiose one [ 49 ].…”
Section: Discussionmentioning
confidence: 92%
“…We assumed dispositional factors that people already possess before searching for and perceiving a calling might influence the relationship between perceiving a calling and OP. For instance, among workers with a strong calling, those with perfectionism, neuroticism, narcissism, and conscientiousness tend to develop OP and exhibit workaholic behaviors [19,26,48]. That is, when those who possess such dispositional factors start to passionately pursue their calling, the possibilities of developing OP and workaholic behaviors might increase.…”
Section: Discussionmentioning
confidence: 99%
“…Snir and Harpaz introduced the concept of HWI-investing both time and effort in work-to unify the concepts of workaholism and work engagement. According to this theoretical perspective [10,26], workaholism and work engagement can also be viewed as negative and positive types of HWI, respectively. HWI research has focused on how workaholism and work engagement lead to different work-related outcomes such as well-being [25] and performance [27].…”
Section: Hwi (Workaholism and Work Engagement)mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have examined the causes and consequences of workaholism. Research has revealed a number of predictors of workaholism such as perfectionism [ 6 , 19 ], self-efficacy [ 20 , 21 ], narcissism [ 22 , 23 ], conscientiousness [ 24 , 25 ], and overwork climate [ 26 ]. Research has also found that workaholism is detrimental to both individuals and organizations.…”
Section: Introductionmentioning
confidence: 99%